Néhány katolikus szemléletű megfontolás az ószövetségi ‘berit’ sajátos relacionális jellegéről - Frivaldszky, János (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
In Deuteronomy, this form of 'covenant' appears as dominant: "you shall be my people". This formula therefore establishes that Israel is God's people. It is a gift by which the Lord has chosen Israel from among many peoples. Thus the chosen people become God's property (segullah), an inheritance. The formal act of the covenant is given meaning and significance insofar as it establishes the life of the covenant relationship and provides its framework, but the emphasis here is on the covenant relationship itself, its inner life.